Phospholipids of Synaptic Membranes in the Pathogenesis of Encephalopathy During Hemorrhagic Shock (Review) - G. F. Leskova (Общая реаниматология)
Correction of brain cell damages caused by massive blood loss is one of the urgent problems of hemorrhagic shock, which ensures the need in clarification of mechanisms of such damages with the prospect of developing strategies to restore the functional activity of neurons. Analysis of the data presented in the review suggests that the dysregulation of phospholipid metabolism underlies both structural damage of synaptic membranes and their functions, including receptor signaling, the disturbances of which lead to encephalopathy in hemorrhagic shock. Correction of synaptic membranes phospholipid composition seems to possess a potential for increasing the effectiveness of treatment of shock-induced brain function disorders.